FENOMENA ‘BLACK SWAN’ DALAM KISAH ADA APA DENGAN CINTA? - Dahlan, Dahri (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2016)
This paper analyzed the ‘black swan’ phenomenon in the story “Ada Apa dengan Cinta?” ‘Black swan’ phenomenon is an event with a content structure that has three characteristics: (1) it is different from the others and unpredictable, (2) it has major effect, and (3) after the event happened, it finally becomes explainable and predictable. The analysis of the phenomenon in the story was conducted using structuralism approach that covers the theory of plot and character. Both theories are used since plot makes the story flows and characters play the plot. As the result of the analysis, it was found that the never-predicted events, which caused major effect to the character Cinta, were in fact explainable and predictable.Keywords: Black swan phenomenon, major effect, structuralism, plot, character.